New progress on the role and mechanism of tau protein in Alzheimer's disease and depression - Wang, Yamei; Zhou, Jinglian; Zhou, Qingqing; Wang, Hua (Frontiers in Neurology, 2025)
Alzheimer's disease (AD) is an age-related neurodegenerative disease characterized by two major pathological hallmarks: (1) the formation of extracellular β-amyloid (Aβ) plaques; (2) the accumulation of intracellular neurofibrillary tangles (NFTs) composed of phosphorylated tau. The number of NFTs is positively correlated with the severity of AD. However, there are still no effective strategies to treat or slow AD progression. Despite recent approvals of anti-Aβ therapies, their limited clinical benefit has shifted increasing attention toward tau pathology as a parallel driver of AD progression. In recent years, the importance of tau in the pathogenesis of Alzheimer's disease increasingly recognized. The transmission of pathogenic tau proteins in the brain, known as prion-like seeding, is considered a key driving factor for AD. Post-translational modifications of tau—such as hyperphosphorylation, acetylation, glycosylation, ubiquitination, and truncation—promote the onset and progression of Alzheimer's disease. Consequently, tau-targeting therapies have become a major focus in anti-AD research, though most remain at the pre-clinical stage. Furthermore, depression is highly prevalent in AD patients, representing both a potential risk factor and a consequence of the disease. Depression is a risk factor of AD, it is also a consequence of AD. Researchers have found that tau is closely related to depression, not Aβ. This review will focus on tau, tau and AD, post-translational modification of tau, tau targeting strategies, and the role of tau in depression. Since tau pathology not only disrupts synaptic and neuronal networks but also affects limbic and cortical circuits involved in emotion regulation, its dysfunction may underlie depressive symptoms frequently observed in AD. Therefore, understanding tau's neural impact provides a mechanistic bridge between AD pathology and depression.